Analysis of Load Sharing Performance of Planetary Gear Reducer in Electric Vehicle Hub Motor - Zhang Jiang; Qing Xunpeng; Chen Haoran (Jixie chuandong)
As for the floating planetary gear reducer in hub motor,a dynamics equation of dual floating planetary transmission system is established,and then the calculation formula of load sharing coefficient is deduced. The simulation of dynamic meshing force between teeth is conducted to evaluate the effect of different types of floating structure of planetary gear meshing both inside and outside on the system load with regard to the angular velocity and contact forces. The simulation results show that the planetary gear angular speed of the double floating type planetary gear system tends to be more consistent,less fluctuation and mutation during the operation process. The planetary gear force distribution is more uniform. It has the minimum load coefficient and the load sharing performance is significantly better than that of free floating and single floating planetary gear structure. This results provide supports for the selection and load sharing design of the planetary gear reducer for the hub motor.